Strategi Pemerintah dalam Penertiban dan Penataan Pedagang Kaki Lima di Pasar Susumbolan Kabupaten Tolitoli - Fitri S Kasim; Selviyana R Manan (Jurnal Multidisiplin Madani, 2022)
This study aims to find out how the Government's Strategy in Controlling and Structuring Street Vendors in Susumbolan Market, this study uses qualitative descriptive. The obstacles encountered in the field are the lack of communication carried out by the government in controlling and structuring street vendors, lack of awareness of traders, lack of facilities and infrastructure. Efforts made by the government in controlling and structuring street vendors are through increasing socialization to street vendors. From the results of the study, it can be concluded that the Government's Strategy in Controlling and Structuring Street Vendors in the Susumbolan Market can be said to be quite good.